Industry Agglomerations and Regional Development in Hungary Economic Processes during European Integration - Wandel, Cordula (Free online access: JSTOR., 2018)
In context with the Eastern enlargement of the European Union, this research deals with the effects of pre- and post-enlargement integration policies on industry concentration and regional development in Hungary. Economic processes are analysed empirically and by means of regression analyses with a spatial perspective and in the framework of the new economic geography over a time span of almost two decades. The results for the manufacturing industries and for regional specialization show which economic centres played a role for the economic development of the country over time. The roles which agglomerations and regional specialization can play are discussed with a view to the problems of cohesion in Hungary, the enlarged EU and future EU accession countries. The conclusions also take into account the current political and academic debate regarding European regional policy.